African Swine Fever Detection and Transmission Estimates Using Homogeneous Versus Heterogeneous Model Formulation in Stochastic Simulations Within Pig Premises - Ssematimba, Amos; Malladi, Sasidhar; Bonney, Peter J.; Charles, Kaitlyn M. St.; Boyer, Timothy C.; Goldsmith, Timothy; Cardona, Carol J.; Corzo, Cesar A.; Culhane, Marie R. (Research Square, 2022)
This study aimed to assess the impact on within-herd transmission dynamics of African swine fever (ASF) when the models used to simulate transmission assume there is homogeneous mixing of animals within a barn. Barn-level heterogeneity was explicitly captured using a stochastic, individual pig-based, heterogeneous transmission model that considers three types of infection transmission, 1) within-pen via nose-to-nose contact; 2) between-pen via nose-to-nose contact with pigs in adjacent pens; and 3) both between- and within-pen via distance independent mechanisms (e.g., via fomites). Predictions were compared between the heterogeneous and the homogeneous Gillespie models. Results showed that the predicted mean number of infectious pigs at specific time points differed greatly between the homogeneous and heterogeneous models for scenarios with low levels of between pen contacts via distance independent pathways and the differences between the two model predictions were more pronounced for the slow contact rate scenario. The heterogeneous transmission model results also showed that it may take significantly longer to detect ASF, particularly in large barns when transmission predominantly occurs via nose-to-nose contact between pigs in adjacent pens. The findings emphasize the need for completing preliminary explorations when working with homogeneous mixing models to ascertain their suitability to predict disease outcomes.
Keywords: African swine fever; Gillespie algorithm; Heterogeneity; Transmission models; Homogeneous mixing